Métodos de extração de fósforo e micronutrientes em latossolos com uso de energia ultrassônica - Rodrigues, Gabrielly Isaac (2016)
Assessing the soil nutrient availability to plants under lab conditions is one of the main challenges to Soil Fertility and Chemistry, due to the complex behavior and the interaction of the soil properties. Many extractant solutions associated with mechanical forms of agitation have been proposed, showing different correlations with plant growth and nutrients absorption. Using ultrasonic energy is a agitation procedure of the soil:extractant solution suspension (based on the cavitation phenomenon). It allows the establishment of relations between the amount of extracted nutrient and the ultrasonic energy level. Thus, this work aims: to evaluate the effect of cavitation intensity on the extraction of P, Zn, Cu, Mn and Fe in soil samples from five Latosols under different uses around Uberlândia and Uberaba, Minas Gerais State; to obtain extracting curves as function of ultrasonic energy levels; and to obtain an index from extracting curves to expresses the nutrient retention by the soil solid phase. A soil-solution suspension (ratio 1:10) was sonicated using a probe ultrasound equipment under different combinations of power and time: i) 30 W for 35, 70, 140 and 280 s; ii) 50 W for 21, 42, 84 and 168 s; and iii) 70 W for 15, 30, 60 and 120 s. The extractant solutions used were Mehlich-1 (for all elements), Olsen and distilled water for P. After each sonication, P concentration was quantified by molybdenum blue colorimetric method and Zn, Cu, Mn and Fe by flame atomic absorption spectrophotometry. The cavitation intensity did not affect the P extraction, only the total energy applied. The P extraction was influenced by extractant solution, decreasing as follows: Mehlich-1>Olsen>water. In cultivated Latosols, the P extraction increased linearly with ultrasonic energy, and the slope of the 1:1 linear regression reflects the P retention in the soil. The Zn and Fe extractions were influenced only by total energy applied. Mn and Cu extractions were influenced by both cavitation intensity and total ultrasonic energy. Soils containing similar amounts of P, Cu, Zn, Mn, and Fe may have a different extraction rate. Likewise, soils containing different amounts of those elements may have the same extraction rate.